Paw patrol. Pups save Puplantis [videorecording (DVD)]. (Paw Patrol, 2019)
The PAW Patrol is diving back in for six underwater adventures! Join Marshall, Chase, Zuma, Skye, Rubble, and Rocky as they save Puplantis, rescue a wiggly whale, and save the Sea Patroller from pirates!